Relation of susceptibility-weighted imaging findings with histological grade in intracranial meningiomas (Annals of Medical Research, 2021)
Aim: We aimed to investigate the relation of susceptibility-weighted imaging (SWI) findings with histological grade in intracranial meningiomas. Materials and Methods: Histopathologically confirmed 58 intracranial meningioma patients (48 typical (low-grade meningioma), 10 atypical (high-grade meningioma)) who had undergone preoperative SWI between 2015 and 2020 were retrospectively evaluated. Tumor size, location, presence of peritumoral edema, WHO grade, low-grade meningioma subtypes and Ki-67 proliferation indexes were noted. SWI findings of intracranial meningiomas were categorized as either positive or negative based on presence/absence of intratumoral susceptibility signals (ITSSs). The origin of ITSSs in SWI-positive meningiomas was assessed with phase images and classified as calcification (SWI-C), vascular structure (SWI-V) or hemorrhage (SWI-H). Mann-Whitney U, chi-square, Fisher’s exact tests and multiple logistic regression analyses were performed for statistical assessment. Results: There was a significant association between SWI-positivity and low-grade in meningiomas (p = 0.010). A higher incidence of calcification was found in low-grade meningiomas (%60 in low-grade vs %10 in high-grade). Peritumoral edema was found to be associated with high grade in meningiomas (p = 0.032). Ki-67 proliferation index was significantly higher in high-grade meningiomas compared to low-grade. (p = 0.000). Conclusion: SWI combined with peritumoral edema may help to predict high grade in intracranial meningiomas.
Keywords: Grade; magnetic resonance imaging; meningioma; susceptibility-weighted imaging